Gamificação no ensino de Física aplicada no Ensino Fundamental II - FERREIRA JÚNIOR, Máximo de Campos (2022)
This teaching work aims to assist the student in the fundamental concepts of Physics in elementary school with the Earth and Universe theme based on BNCC and aimed at the 6th grade using gamification in Physics and Physics simulators. Aiming at the student's reasoning and understanding of reading, interpreting and defining Physics concepts based on the classes taught during the Physics teaching project at school. This project was fundamentally based on gamification, which consists of putting the teacher in an active role in the elaboration of activities and aims to explore the didactic aspects relevant to the teaching process that allow the teacher to use various learning possibilities, since gamification together with the Physics simulators draws students' attention so that they can learn while playing.